EXCLI Journal; 22:Doc295; ISSN 1611-2156 2023
DOI: 10.17179/excli2022-5667
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil does not affect human microglial immune activation in response to pro-inflammatory cytokines

Abstract: Remifentanil is a potent ultra-short acting μ-opioid analgesic drug, frequently used in anaesthesia due to its favorable pharmacodynamic and pharmacokinetic profile. It may be associated with the occurrence of hyperalgesia. Preclinical studies suggest a potential role of microglia, although the molecular mechanisms have not been fully elucidated. Considering the role of microglia in brain inflammation and the relevant differences among species, the effects of remifentanil were studied on the human microglial C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“… 14 However, when we further expanded these initial observations, focusing on proinflammatory mediators, we demonstrated that RF, at clinically relevant concentrations, is not able to directly modulate the immune activation of human microglia. 19 …”
Section: Discussionmentioning
confidence: 99%
“… 14 However, when we further expanded these initial observations, focusing on proinflammatory mediators, we demonstrated that RF, at clinically relevant concentrations, is not able to directly modulate the immune activation of human microglia. 19 …”
Section: Discussionmentioning
confidence: 99%
“…However, we have recently shown that RF is not able to directly modulate the immune activation of human microglia at clinically relevant concentrations, although it may exert direct pro-nociceptive effects, through activation of the brain-derived neurotrophic factor signaling pathway. [ 51 52 53 ] The rate POCD did not vary when RF was used combined with different modalities of general anesthesia, i.e., sevoflurane-based (volatile) anesthesia versus propofol-based anesthesia (total intravenous anesthesia). [ 54 ] The study enrolled patients with coronary artery disease (CAD) undergoing non-cardiac interventions.…”
Section: Literature Searchmentioning
confidence: 99%
“…[ 57 ] This finding is also confirmed by preclinical studies on human microglia due to the lack of any toxic effect or neuroinflammatory action on the central nervous system (no effect on inflammatory mediators) but, rather, a neuroprotective action throughout the induced rise in basal BDNF production. [ 58 59 ]…”
Section: Introductionmentioning
confidence: 99%